2014
DOI: 10.1039/c4an00108g
|View full text |Cite
|
Sign up to set email alerts
|

Design and study of the efflux function of the EGFP fused MexAB-OprM membrane transporter in Pseudomonas aeruginosa using fluorescence spectroscopy

Abstract: Multidrug membrane transporters (efflux pumps) can selectively extrude a variety of structurally and functionally diverse substrates (e.g., chemotoxics, antibiotics), leading to multidrug resistance (MDR) and ineffective treatment of a wide variety of diseases. In this study, we have designed and constructed fusion gene (egfp-mexB) of N-terminal mexB with C-terminal egfp, inserted it into a plasmid vector (pMMB67EH), and successfully expressed it in ΔMexB (MexB deletion) strain of Pseudomonas aeruginosa to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Thus, the PBS buffer (but not cell culture medium) was used to suspend the bacterial cells for the study of accumulation kinetics of pump substrates over time, as those reported previously. 14, 15, 24, 25, 33, 35, 37 Note that the cells would grow in the culture medium, and the number of the cells would change over time, making the study of the accumulation rates of single NPs in the cells over time impossible. Our studies demonstrate that the bacterial cells remain alive and retain their efflux functions in the PBS buffer, as shown in Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the PBS buffer (but not cell culture medium) was used to suspend the bacterial cells for the study of accumulation kinetics of pump substrates over time, as those reported previously. 14, 15, 24, 25, 33, 35, 37 Note that the cells would grow in the culture medium, and the number of the cells would change over time, making the study of the accumulation rates of single NPs in the cells over time impossible. Our studies demonstrate that the bacterial cells remain alive and retain their efflux functions in the PBS buffer, as shown in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…9-15 These conventional methods enable one to study ensemble accumulation kinetics of bulk cells. We have also demonstrated that thin-layer total-internal reflection fluorescence microscopy and spectroscopy can be used to measure efflux kinetics of single membrane transporters of single live cells in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…1415, 1819, 29, 61 The previous studies have showed that the bacterial cells in the PBS buffer retain their efflux function over hours. 1415, 1819, 29, 61 Notably, the bacterial cells suspended in the PBS buffer retain their cellular growth stage and cellular function over hours, and their number remains the same over time.…”
Section: Methodsmentioning
confidence: 99%
“…1415, 1819, 29, 61 The previous studies have showed that the bacterial cells in the PBS buffer retain their efflux function over hours. 1415, 1819, 29, 61 Notably, the bacterial cells suspended in the PBS buffer retain their cellular growth stage and cellular function over hours, and their number remains the same over time. 1415, 1819, 29, 61 Therefore, in order to use the same growth stage and number of the cells over the duration of each experiment (2 h), it is essential to study the accumulation rates of the NPs in the cells that are suspended in the PBS buffer, but not in the cell culture medium which would lead to the cell growth and creation of the cells with various growth stages and functions.…”
Section: Methodsmentioning
confidence: 99%
“… 61 66 Some literature has also reported the changes in the biological property of the sample after fluorescence labeling. 67 , 68 Similarly, the radio ligand binding assay 69 produces toxic radioactive wastes which are extremely harmful to in vivo studies. Although the above-mentioned techniques are useful to screen the binding specificity of signaling molecules such as drugs and neurotransmitters, they suffer from some serious limitations.…”
Section: Introductionmentioning
confidence: 99%